Philosophical Consulting as a Tool for “Problem Hacking” in Human Management in Organizations - O. E. Ivanova (Управленческое консультирование, 2021)
Consulting focused on comprehending organizational problems and breaking the patterns of their managerial solution is in demand in a chaotic, dynamic world. This counseling tool is able to counter the uncertainty of the external environment with a clear understanding of the or ganizational event. The aim of the paper is to investigate philosophical consulting as an intellectual tool for “problem hacking” in Human Management in organization.Theoretical basis of the research: the analytical approach to human resource management, the ideas of the international movement of philosophical practice, the edifying philosophy of R. Rorty, ideas of “problem hacking”. Research methods used in the work: philosophical (conceptual) analysis, decomposition, conceptualization.Results. Philosophical consulting is justifed as an analytical and value-based tool of facilitation of “problem hacking” in Human Management in the organization, the features of philosophical consulting as a management consulting are revealed. With the purpose of hacking problems at the level of foundations — meanings and values — according to each stage of “problem hacking”, the function of facilitation of philosophical consulting is revealed. HRMproblems are classifed into process groups: “cooperation”, “change and development”, “measurement and evaluation”. Typical HR-challenge are identifed — the feld of potential conﬂicts.The concept of HR-call is formulated and elements of the problem solution construction are developed: philosophical idea of the answer to HR-challenge and relevant managerial methods of realization.Application of value-analytical and design tools of philosophical consulting to “hacking” organizational problems — the company’s response to the challenges of the VUCA world, “defcit of meaning” in Russian companies, the employers’ demand for problem-solving skills in the next fve years. The limitations of the research are identifed.